A torch against the night : an ember in the ashes novel - Tahir, Sabaa; Tahir, Sabaa ([New York, New York] : Razorbill, an imprint of Penguin Random House, 2016)
After the events of the Fourth Trial, Martial soldiers hunt the two fugitives as they flee the city of Serra and undertake a perilous journey through the heart of the Empire
Laia is determined to break into Kauf - the Empire's most secure and dangerous prison - to save her brother, who is the key to the Scholars' survival. And Elias is determined to help Laia succeed, even if it means giving up his last chance at freedom. But dark forces, human and otherworldly, work against Laia and Elias. The pair must fight every step of the way to outsmart their enemies: the bloodthirsty Emperor Marcus, the merciless Commandant, the sadistic Warden of Kauf, and, most heartbreaking of all, Helene - Elias's former friend and the Empire's newest Blood Shrike. Bound to Marcus's will, Helene faces a torturous mission of her own - one that might destroy her: find the traitor Elias Veturius and the Scholar slave who helped him escape... and kill them both
Maps on lining papers
Keywords: Laia (Fictitious character) -- Fiction; Elias (Fictitious character) -- Fiction; Fugitives from justice -- Fiction; Brothers and sisters -- Fiction; Fantasy; Romance fiction; Fugitives from justice -- Juvenile fiction; Prisons -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Young adult fiction